The Cultural Aspects of Antanas Krishchukajtis-Aishbe’s Translation of Yu. Fedkovych’s Story "Who is to Blame"? - Пахолок, Зинаида (Literatūra, 2017)
The cultural, historical and sociological determinants of A. Krishсhukajtis-Aishbe as an interpreter are considered in this article. His literary pseudonym’s translation into Russian, which was based on the structural and semantic principle of education, was refined. Particular attention is paid to the story Who is to Blame? by Yu. Fedkovych. The Ukrainian writer raised an issue of universal character, a dream of happiness and the family circumstances that prevent it. Then, I. Franco investigated the same issue in the play Stolen Happiness, staged in Panevėžys. An acquaintance of A. Krishсhukajtis-Aishbe with the story Who is to Blame? was held indirectly, with the help of the Russian translation by N. N. Zlatovratsky. It is established that the basis of the two translations is identical in its sociohistorical conditions and the psychological similarity of artistic thinking of the creative natures in solving the main issue in literature: of the person and the surrounding reality. The interpretation of A. Krishсhukajtis-Aishbe, connected with the transformation nominations of the characters and of the locations in the translation, is analyzed.ANTANO KRIŠČIUKAIČIO-AIŠBĖS ATLIKTO J. FEDKOVIČIAUS APSAKYMO „KAS КАLTAS?“ VERTIMO KULTŪRINIAI ASPEKTAIStraipsnyje nagrinėjami kultūriniai, istoriniai ir sociologiniai veiksniai, turėję lemiamą įtaką lietuvių rašytojo Antano Krikščiukaičio vertimo veiklai. Patikslintas jo literatūrinio slapyvardžio, sukurto remiantis struktūriniu-semantiniu principu, vertimas į rusų kalbą. Ypatingas dėmesys skiriamas J. Fedkovičiaus apsakymui „Kas kaltas?“ Ukrainiečių rašytojas į apsakymo centrą iškėlė bendražmogiškas problemas – svajonę apie laimę ir jai kliudančias šeimines aplinkybes. Vėliau šią problemą gvildeno I. Franko Panevėžyje pastatytoje pjesėje „Pavogta laimė“. A. Krikščiukaitis-Aišbė pirmiausia susipažino su apsakymo „Kas kaltas?“ vertimu į rusų kalbą, atliktu N. N. Zlatovrackio. Nustatyta, kad abu vertimai artimi identiškomis juos lėmusiomis socialinėmis-istorinėmis sąlygomis ir meniškos prigimties asmenybėms būdingo kūrybinio mąstymo psichologiniu panašumu sprendžiant literatūroje dominuojančią žmogaus ir tikrovės priešstatos problemą. Straipsnyje išanalizuota A. Krikščiukaičio-Aišbės J. Fedkovičiaus apsakymo interpretacija, susijusi su veikėjų nominacijų ir tekste esančių lokacijų transformacija.
Keywords: interpreter; literary pseudonym; story; play; interpretation; culturology